Two cases of spontaneous remission of primary hyperparathyroidism due to auto-infarction: different management and their outcomes. (7th May 2019) - Novodvorsky, Peter; Hussein, Ziad; Arshad, Muhammad Fahad; Iqbal, Ahmed; Fernando, Malee; Munir, Alia; Balasubramanian, Sabapathy P
Summary: Spontaneous remission of primary hyperparathyroidism (PHPT) due to necrosis and haemorrhage of parathyroid adenoma, the so-called 'parathyroid auto-infarction' is a very rare, but previously described phenomenon. Patients usually undergo parathyroidectomy or remain under close clinical and biochemical surveillance. We report two cases of parathyroid auto-infarction diagnosed in the same tertiary centre; one managed surgically and the other conservatively up to the present time. Case #1 was a 51-year old man with PHPT (adjusted (adj.) calcium: 3.11 mmol/L (reference range (RR): 2.20–2.60 mmol/L), parathyroid hormone (PTH) 26.9 pmol/L (RR: 1.6–6.9 pmol/L) and urine calcium excretion consistent with PHPT) referred for parathyroidectomy. Repeat biochemistry 4 weeks later at the surgical clinic showed normal adj. calcium (2.43 mmol/L) and reduced PTH. Serial ultrasound imaging demonstrated reduction in size of the parathyroid lesion from 33 to 17 mm. Twenty months later, following recurrence of hypercalcaemia, he underwent neck exploration and resection of an enlarged right inferior parathyroid gland. Histology revealed increased fibrosis and haemosiderin deposits in the parathyroid lesion in keeping with auto-infarction. Case #2 was a 54-year-old lady admitted with severe hypercalcaemia (adj. calcium: 4.58 mmol/L, PTH 51.6 pmol/L (RR: 1.6–6.9 pmol/L)) and severe vitamin D deficiency. She was treated with intravenous fluids and pamidronate and 8 days later developed symptomatic hypocalcaemia (1.88 mmol/L) with dramatic decrease of PTH (17.6 pmol/L). MRI of the neck showed a 44 mm large cystic parathyroid lesion. To date, (18 months later), she has remained normocalcaemic. Learning points: Primary hyperparathyroidism (PHPT) is characterised by excess parathyroid hormone (PTH) secretion arising mostly from one or more autonomously functioning parathyroid adenomas (up to 85%), diffuse parathyroid hyperplasia (<15%) and in 1–2% of cases from parathyroid carcinoma. PHPT and hypercalcaemia of malignancy, account for the majority of clinical presentations of hypercalcaemia. Spontaneous remission of PHPT due to necrosis, haemorrhage and infarction of parathyroid adenoma, the so-called 'parathyroid auto-infarction', 'auto-parathyroidectomy' or 'parathyroid apoplexy' is a very rare in clinical practice but has been previously reported in the literature. In most cases, patients with parathyroid auto-infarction undergo parathyroidectomy. Those who are managed conservatively need to remain under close clinical and biochemical surveillance long-term as in most cases PHPT recurs, sometimes several years after auto-infarction.